Alemanha: Mitos, fatos e desafios para o século XXI - Licio da Costa Raimundo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The text works with the German development way after the end of the Great War II. It`s sustained that the well-doing of the Social Market Economy is due to the particular moment of the Cold War and the specific role of Germany on it. It was possible for Germany built a strong economy and a fair society even in the absence of one strng State. After the fall of the Berlin Wall, Germany entered on the process of unification and came in the European Union putting end on the basis of the Social Market Economy and replacing it by what F. Mitterrand called once the Europe of marchands. The present crisis is the reflect of this historical trajectory.
Keywords: F55; 330